Genetic Characterization of a Pigeon Paramyxovirus Type 1 Isolated from Columba livia in Uruguay - Castro, E. R. (2012)
The isolation and molecular characterization of pigeon paramyxovirus type 1 (PPMV-1) from a sick racing pigeon in Uruguay is reported for the first time. Hemagglutination inhibition (HI) tests were performed to detect antibodies against avian paramyxovirus serotype 1 (APMV-1), and a HI titer of 1/32 was obtained. Tracheal and cloacal swabs were processed by real-time reverse transcriptionpolymerase chain reaction (rRT-PCR) with the use of the National Veterinary Services LaboratoryU.S. Department of Agriculture validated matrix (M) gene assay and were positive for APMV-1. Viral isolation in embryonated chicken eggs confirmed the molecular detection of the isolate. A fragment corresponding to the 3' region of the fusion (F) protein gene was amplified by RT-PCR, and subsequently sequenced. The deduced amino acid sequence at the F protein cleavage site displayed the motif 112RRQKR/F 117. Phylogenetic analysis of this part of the genome allowed the isolated virus to be grouped in the lineage VIb/4b, which suggests that it shares the same ecologic niche with other PPMV-1 that were found in the region, and it is not imported as other European or North American viruses.